On the Dimers Stability of Allicin and Its Derivatives Interacting with AT, GC, and DNA Bridge: DFT Study - Mindaugas Macernis (Journal of Chemistry)
Allicin and its derivatives are physiologically active molecules with many potential health benefits. It is not clear if they have a direct effect on DNA or protein. In order to elucidate the allicin and its derivatives’ effect on DNA base pairs, we investigated various complexes of base pair and its bridge with an allicin and its derivatives. The investigated allicin derivatives were (E)-Ajoene, (Z)-Ajoene, Amz121, and Bmz73 radicals. The DFT calculation results revealed that the investigated molecules would favor binding to bridge of the base pairs instead of directly affecting the base pairs. The Bmz73 radical could break DNA by change bonding in it because the Bmz73 radical significantly affected the P-O bond of the bridge of base pair.